2011
DOI: 10.4269/ajtmh.2011.11-0145
|View full text |Cite
|
Sign up to set email alerts
|

HMS-Related Hemolysis after Acute Attacks of Plasmodium vivax Malaria

Abstract: Among a cohort of 1,213 cases treated for Plasmodium vivax malaria from an isolated Papua New Guinean population, seven adults with severe and sustained hemolytic anemia after clearance of the peripheral parasitemia were prospectively investigated. All the patients fulfilled the criteria for hyper-reactive malarial splenomegaly and in 2 of 7 cases an IgG warm antibody was identified. Hereditary hemolytic anemia was excluded in 5 of 5 patients. All treated cases improved after an initial high dose of prednisone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Classically HMS was associated mostly with Plasmodium malariae, but a population-based study in Papua New Guinea showed that P. vivax could also cause HMS. 17 There are a few populations that, due to historical transpositions, have recreated pre-modern malaria conditions while still having malariometric indices that may be informative regarding malaria-associated mortality. Allied prisoners of war (POWs) on the Thai-Burma railway suffered huge casualties due to a combination of malnutrition, injury, and infection with tropical diseases.…”
Section: Exclusions and Modern Populationsmentioning
confidence: 99%
“…Classically HMS was associated mostly with Plasmodium malariae, but a population-based study in Papua New Guinea showed that P. vivax could also cause HMS. 17 There are a few populations that, due to historical transpositions, have recreated pre-modern malaria conditions while still having malariometric indices that may be informative regarding malaria-associated mortality. Allied prisoners of war (POWs) on the Thai-Burma railway suffered huge casualties due to a combination of malnutrition, injury, and infection with tropical diseases.…”
Section: Exclusions and Modern Populationsmentioning
confidence: 99%
“…Des cas chez des patients infectés par Plasmodium malariae et Plasmodium vivax ont été rapportés [5][6][7] mais il est possible que la SPH ait été due à une co-infection par P. falciparum à bas niveau non diagnostiquée.…”
Section: éLéments De Physiopathologieunclassified
“…The most common presenting symptoms of TSS are chronic abdominal swelling (64%) and dragging abdominal pain (52%), mainly during adult life [ 8 ]. Almost all patients (97%) have weight loss.…”
Section: Reviewmentioning
confidence: 99%